Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Redox and selective oxidation properties of Mn complexes grafted on SBA-15 - Saikia, Lakshi; Srinivas, D. (Catalysis Today, 2009)
Manganese complexes of 5,10,15,20-tetraphenylporphyrin (Mn(TPP)Cl) were grafted on SBA-15 functionalized with propyl-amine, -thiol and -sulfonic acid groups. The acido-basic properties of the support influenced the oxidation state, redox behavior and selective oxidation properties of the Mn complexes. Acidic supports (SBA-15-pr-SH and SBA-15-pr-SO(3)H) promoted the reduction of Mn ions in Mn-TPP complexes from 3+ to 2+ oxidation state. A similar behavior was found also when Mn(Salen)Cl complexes were immobilized on those supports. However, the extent of such facile reduction was more in the case of Mn-TPP than in Mn-Salen complexes. The former exhibited superior catalytic activity (turnover frequency) than the latter-type Mn complexes in regio-, stereo- and chemoselective oxidation of R-(+)-limonene with molecular oxygen (1 atm) at ambient temperatures. The catalytic oxidation activity correlates with the redox behavior of the grafted Mn complexes. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Grafted manganese complexes; Mn(Salen)Cl; Mn(TPP)Cl; Organo-functionalized SBA-15; Redox behavior of Mn; Selective oxidation of limonene

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides